Consumer Protection through Regulation of Non-Conforming Products in Online Purchase Transactions - Siregar, Dahris; Harahap, Faisal Sadat Soaduon (Indonesian Journal Publisher, 2025)
: The purpose of this study is to investigate how consumers might be protected against improper products when purchasing and selling online. Examining the type and extent of legal protections available to consumers and sellers of non-conforming items is the main goal of this study. A clear understanding of the rights and obligations of consumers and sellers in online transactions is very important. This study uses a normative juridical approach. A normative legal research technique, which entails a qualitative examination of the legal norms found in existing laws and regulations, is employed in this study. The obligations of business actors and consumer legal protection against inappropriate products during online transactions are the main topics of this study. The results of the study show that customers are entitled to products that reflect their preferences, and sellers in the market will be held liable for such errors under the Consumer Protection Act if the goods sold do not match. In order to boost transparency and customer trust, e-commerce also plays a significant role in advising manufacturers to make sure that the pictures of the products being promoted appropriately reflect their state and in promoting the usage of actual product photos. Buyers can take legal action, both litigation and non-litigation, if the goods sold do not match the drawings.